Buckling optimization of laminated truncated conical shells subjected to external hydrostatic compression. (15th February 2018) - Hu, Hsuan-Teh; Chen, Hsien-Chih
Abstract: Buckling analyses of laminated truncated conical shells subjected to external hydrostatic compression are carried out by employing the Abaqus finite element program. The critical buckling loads of these truncated conical shells with a given material system are maximized with respect to fiber orientations by using the golden section method. Through parametric studies, the influences of the end condition, shell thickness, shell length, shell radius ratio and cutout size on the optimal buckling loads, the associated optimal fiber orientations and the associated buckling modes are demonstrated and discussed.